2022
DOI: 10.3947/ic.2021.0142
|View full text |Cite|
|
Sign up to set email alerts
|

Fluvoxamine Treatment of Patients with Symptomatic COVID-19 in a Community Treatment Center: A Preliminary Result of Randomized Controlled Trial

Abstract: Background This study aimed to evaluate whether fluvoxamine reduces clinical deterioration in adult patients with mild to moderate coronavirus disease 2019 (COVID-19), and to identify risk factors for clinical deterioration in patients admitted to a community treatment center (CTC). Materials and Methods A randomized, placebo-controlled trial was conducted in a CTC, in Seoul, Korea from January 15, 2021, to February 19, 2021. Symptomatic adult patients with positive res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
66
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(70 citation statements)
references
References 26 publications
4
66
0
Order By: Relevance
“… 8 It was stopped early for operational reasons, 8 and the primary outcome (defined as in the Stop COVID trials) was observed in 2/26 treated and 2/26 placebo patients. 8 Figure 1 depicts meta‐analysis of study‐defined primary outcomes and of hospitalizations that uses the same frequentist and Bayesian methodology as used by Lee et al . 3 except that it includes the Korean data 8 and employs Hartung–Knapp–Sidik–Jonkman correction shown to improve confidence interval coverage with small number of trials differing in size 9 : (i) for both outcomes, frequentist point‐estimates are closely similar to those published, 3 , 4 but indicators of uncertainty are more obvious—CIs are wider (and embrace unity; imprecision), and prediction intervals are wide (heterogeneity; Figure 1 ); (ii) Bayes point‐estimate for hospitalizations (Figure 1B ) indicates somewhat less risk reduction (RR = 0.819) than published 3 (RR = 0.78) and CIs and (wide) prediction intervals are shifted to the right (imprecision, heterogeneity).…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“… 8 It was stopped early for operational reasons, 8 and the primary outcome (defined as in the Stop COVID trials) was observed in 2/26 treated and 2/26 placebo patients. 8 Figure 1 depicts meta‐analysis of study‐defined primary outcomes and of hospitalizations that uses the same frequentist and Bayesian methodology as used by Lee et al . 3 except that it includes the Korean data 8 and employs Hartung–Knapp–Sidik–Jonkman correction shown to improve confidence interval coverage with small number of trials differing in size 9 : (i) for both outcomes, frequentist point‐estimates are closely similar to those published, 3 , 4 but indicators of uncertainty are more obvious—CIs are wider (and embrace unity; imprecision), and prediction intervals are wide (heterogeneity; Figure 1 ); (ii) Bayes point‐estimate for hospitalizations (Figure 1B ) indicates somewhat less risk reduction (RR = 0.819) than published 3 (RR = 0.78) and CIs and (wide) prediction intervals are shifted to the right (imprecision, heterogeneity).…”
Section: Figurementioning
confidence: 99%
“…Two further points additionally illustrate current uncertainty about the effect of fluvoxamine. First, the proportions reported in the 2 smaller trials (Stop COVID 1, 5 signalling a potentially large benefit and the Korean trial 8 signalling no potential benefit) are fragile (numerically unstable): it can be shown that even under the assumption of a marked fluvoxamine effect 1 or 2 events more in the fluvoxamine arms and 1 or 2 fewer in the placebo arms would be equally as probable as the observed numbers of events. Next, estimates of heterogeneity across trials that substantially differ in size are problematic.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…We would like to correspond and share ideas on the publication “Fluvoxamine treatment of patients with symptomatic COVID-19 in a community treatment center: a preliminary result of randomized controlled trial” [ 1 ]. According to Seo et al, there were no significant differences in clinical worsening between patients treated with fluvoxamine and those treated with a placebo in this research of adult patients with symptomatic coronavirus disease 2019 (COVID-19) who were admitted to the community treatment center [ 1 ]. There are several new proposed alternative treatments against COVID-19, including fluvoxamine.…”
mentioning
confidence: 99%
“…In the TOGETHER trial, enrolled patients had at least one criterion for high risk; diabetes, systemic arterial hypertension requiring at least one medication, known cardiovascular diseases, symptomatic lung diseases, smoking, obesity, having had a transplant, chronic kidney disease, immunosuppressive therapy, history of cancer or aged 50 years or older. However, we enrolled adult patients admitted to a community treatment center, who usually had no or minimum comorbidities [ 5 ]. We excluded patients with severe underlying lung diseases, chronic liver diseases, congestive heart failure, chronic kidney disease, or those who were immunocompromised.…”
mentioning
confidence: 99%